A systematic review of inequalities in the use of maternal health care in developing countries: examining the scale of the problem and the importance of context - Say, Lale; Raine, Rosalind (Bulletin of the World Health Organization, 2007)
Two decades after the Safe Motherhood campaigns 1987 launch in India, half a million women continue to die from pregnancy-related causes every year. Key health-care interventions can largely prevent these deaths, but their use is limited in developing countries, and is reported to vary between population groups. We reviewed the use of maternal health-care interventions in developing countries to assess the extent, strength and implications of evidence for variations according to women's place of residence and socioeconomic status. Studies with data on use of a skilled health worker at delivery, antenatal care in the first trimester of pregnancy and medical settings for delivery were assessed. We identified 30 eligible studies, 12 of which were of high or moderate quality, from 23 countries. Results of these studies showed wide variation in use of maternal health care. Methodological factors (e.g. inaccurate identification of population in need or range of potential confounders controlled for) played a part in this variation. Differences were also caused by factors related to health-care users (e.g. age, education, medical insurance, clinical risk factors) or to supply of health care (e.g. clinic availability, distance to facility), or by an interaction between such factors (e.g. perceived quality of care). Variation was usually framed by contextual issues relating to funding and organization of health care or social and cultural issues. These findings emphasize the need to investigate and assess context-specific causes of varying use of maternal health care, if safe motherhood is to become a reality in developing countries.